COMPARISON OF MOTOR ABILITIES OF YOUTH FOOTBALL PLAYERS AND PRIMARY SCHOOL PUPILS - Miroslav Smajić; Dejan Javorac; Slavko Molnar; Aleksandar Huba Barašić; Bogdan Tomić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: Football as a complete sport that is rich in a wide variety of possible movements classified in polistructural, sports complex. To be a football player was able to perform tasks football has, among other things, and have the necessary level of motor abilities that can be achieved only through systematic implementation of training physical training. The aim of this research was to determine the differences in some of the motor abilities between the two researched groups. Methods: In a sample of 196 subjects average age of 12.45 ± 0.03 years, made a comparison of motor abilities. The first group consisted of 82 players - Pioneers FC "Red Star" from Belgrade and the other 114 primary school pupils from Novi Sad. A sample of 9 tests of motor abilities were: long jump from the place, running 20 m, 60 m running, bend straddle the gray, endurance in pull-ups, polygon backwards, slalom with three balls, hand tapping and lifting troops. Comparison of motor abilities of young players and pupils of primary schools was carried out by using multivariate analysis of variance (MANOVA). Results: An analysis of motor abilities between young players and primary school pupils were found statistically significant differences in all tested variables. Discussion: The research has shown that speed, endurance, coordination and muscle strength of the lower leg predominantly responsible for the success of matching the target foot at a distance, which is an integral part of the training process (Smajic and Molnar, 2007). It is also proven that there is a statistically significant correlation between the explosive and repetitive strength as a predictor of outcome-success rate for jumping in the air at youth players (Stankovic, 2011). References: Kuleš, B., Jerkovic, S. Maric, J. (1991). Influence of running different intentiteta to success in football. Kinesiology, 23 (1-2), 60-65. Malacko, J. (2000). Fundamentals of sports training - a quarter-supplemented and revised edition, Belgrade: Sports Academy. Miljkovic, Z., Jerkovic, S. and Šimenc, Z (2002). Evaluation of a model tracking the player of the attacking team and in terms of football matches. Kinesiology, 34 (1), 73-85. Smajić, M. and Molnar, S. (2007). Influence of morphological characteristics and basic motor skills-factor precision of target foot at a lesser distance. In XLVI Congress of Anthropological Society of Yugoslavia with international participation (26-31). Apatin: Anthropological Society of Yugoslavia. Stankovic, D. (2011). Strength as a predictor of success rezultataske high jump. In Proceedings of the FIS komnikacije in sport, physical education and recreation, 232-238, Niš: Faculty of Sport and Physical Education. Vucetic, V., Ivanjko, A. Šentija, D. and Sedar, M. (2003). Speed endurance players, conditioning training of athletes. International Scientific Conference Proceedings. Zagreb: Faculty of Physical Education, University of Zagreb.